PENGEMBANGAN MEDIA RUBIK’S CUBE COLOR FULD TERHADAP KEMAMPUAN PENGENALAN WARNA ANAK USIA DINI - Mukhammad Nurdin Chamim (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2020)
In this advancement is for creating a new learning media for early age children in order to know or to learn about color by using modified cube as the main media. The data collection is from the result of interview session and direct observation in academic class or in home domain. The researcher choose the idea, theme, concept, mind mapping, skecthing, design the wooden cube, coloring, until finalizing the design. The result of the advancement, overall can create a playroom for children that can be used for learning media. The media is deliberate in some ways there are the main media which is rubik cube color fold, with the addition or support by using folden paper like origami and sticker, and intersting case.